2015
DOI: 10.1016/j.cllc.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking Status on EGFR-TKI Efficacy for Advanced Non–Small-Cell Lung Cancer in EGFR Mutants: A Meta-analysis

Abstract: For advanced NSCLC patients with EGFR mutations, nonsmoking is associated with longer PFS than ever smoking after EGFR-TKIs treatment. Smoking history should be considered an essential factor in studies regarding EGFR-targeted agents toward EGFR-mutant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 35 publications
3
46
0
Order By: Relevance
“…Moreover, a previous study identified an inverse relationship between incidence of EGFR mutations and number of pack-years of cigarette smoking, with fewer mutations found in patients with longer smoking history (12). Together, these findings suggest that favorable outcomes in response to EGFR-TKI therapy in non-smoking NSCLC patients are due to their higher rate of EGFR-mutation compared with that of smoking patients (16,17).…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Moreover, a previous study identified an inverse relationship between incidence of EGFR mutations and number of pack-years of cigarette smoking, with fewer mutations found in patients with longer smoking history (12). Together, these findings suggest that favorable outcomes in response to EGFR-TKI therapy in non-smoking NSCLC patients are due to their higher rate of EGFR-mutation compared with that of smoking patients (16,17).…”
Section: Introductionsupporting
confidence: 54%
“…However, in our study, EGFR mutation status had no significant effect on the clinical outcome. Also, recent metaanalyses (17,30) showed that non-smokers are likely to have a longer PFS than smokers when undergoing EGFR-TKI therapy for diagnosed EGFR-mutant NSCLC. A recent study by Mitchell et al (16) concluded that controversies in the survival outcomes of smokers versus non-smokers after EGFR-TKI therapy may be due to incomplete data on smoking history, and that its relationship with treatment response has not been comprehensively analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR-TKI might be effective in patients with EGFR mutation during the initiation of the treatment since EGFR mutation plays a dominant role. However, resistance to EGFR-TKIs may occur once the dominant carcinogenic effect of EGFR mutations is replaced by other mechanisms; 48 nevertheless, specific mechanisms remain unknown. The poor response to EGFR-TKIs in patients with a smoking history could be explained by cigarette smoking-induced EGFR posttranslational changes, activation of the nicotinic acetylcholine receptor by cigarette smoking-induced EGFR-TKIs resistance, promotion of EGFR signal, and epithelialmesenchymal transition (EMT).…”
Section: Cigarette Smokingmentioning
confidence: 99%
“…A meta-analysis reported that non-smoking is associated with longer PFS than ever smoking after EGFR-TKIs treatment in advanced NSCLC patients with EGFR mutations. 48 The dosage of smoking may affect the EGFR-TKIs efficacy. The smoking dosage of ≥30 pack-years is an independent negative predictor of the efficacy of EGFR-TKIs in lung adenocarcinoma patients with activating EGFR mutations.…”
Section: Cigarette Smokingmentioning
confidence: 99%